(untitled) (Docentes 2.0 Journal, 2024)
Technology has integrated social networks into education, generating benefits to the educational process, such as optimizing communication in the teaching-learning process, involving students in activities, and facilitating access to information, thus improving the learning experience. The study had the objective of analyzing the didactic strategies for continuous improvement in the use of the social network Facebook in 10th-grade students of the Las Nieves District Educational Institution to integrate Facebook into the main axis of social interaction among students to improve academic success, communication with their teachers and family support in the institution by allowing the correct formation of their digital competences. The inquiry was immersed in the interpretative paradigm, located in the qualitative approach of the analytical type, with the bibliographic design of the documentary type being the unit of analysis of the bibliographic sources analyzed and cited in the study. Among its results, the importance of using social networks in the classroom was evidenced; therefore, it was concluded that Facebook had opened a range of possibilities of strategies, methodologies, learning, and multiple means of accessing knowledge at any time and place, which allowed the educational community to create a suitable environment in the implementation of continuous improvement strategies. Likewise, it was recommended that didactic strategies for continuous improvement using the social network Facebook be proposed to 10th-grade students of the I.E.D. Las Nieves.